Współpraca świata nauki z przemysłem spożywczym w ramach projektu POLFOOD na przykładzie Pomorza Zachodniego - Łącka, Irena (Co-Operation of World of Science with Food Industry Withing the POLFOOD Project Example of West Pomerania, 2005)
The article discusses the co-operation of science environment with enterprises of food industry within the POLFOOD project funded from 6th Framework Programme for European Research & Technological
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1070, t. 2, s. 38-44